TRANSLATION TECHNIQUES AND QUALITY OF SPEECH ACTS FOUND IN A WRINKLE IN TIME MOVIE - Salsabila Baiqlis Ramadhanti; Evert Haryanto Hilman; Maftuchah Dwi Agustina (IdeBahasa, 2022)
This research examined the classification of speech acts, the classification of translation techniques used by the translator in transferring speech acts, and the translation quality found in A Wrinkle in Time movie. Descriptive qualitative method used in this research. The source data was taken from English script and Indonesian subtitles of A Wrinkle in Time (2018) movie using Yule, Molina and Albir, and Nababan et al.’s theories. Based on the results, there were five classifications of speech acts that found in 108 data; representative 46 data (42.6%), expressive 27 data (25.0%), directive 24 data (22.3%), commissive 6 data (5.5%), and declaration 5 data (4.6%). Then, there were twelve classifications of translation techniques that found in 150 data; literal translation 70 data (47.0%), reduction 24 data (16.0%), linguistic compression 14 data (9.3%), generalization 8 data (5.3%), amplification 8 data (5.3%), established equivalent 8 data (5.3%), borrowing 5 data (3.3%), modulation 5 data (3.3%), compensation 4 (2.7%), discursive creation 2 data (1.3%), adaptation 1 (0.6%), and adaptation 1 (0.6%). The results of the data have translation quality in three aspects; accuracy, acceptability, and readability.